Respuesta :
Answer:
tA=tB
tB=(sA-dA)/vA watch it below
Explanation:
the spatio for A is sA=vA*tA+dA
the spatio for B is sB=vB*tB
the meeting point will happen at: tA=tB
so, sA=vA*tB+dA
tB=sB/vB
yields:
sA=vA*(sB/vB)+dA
sA-dA=vA*(sB/vB)
sB=(sA-dA)*vB/vA
then
tB=((sA-dA)*vB/vA)/vB
tB=(sA-dA)/vA
The answer is tA=tB
When tB= (sA-dA) /vA watch it below
- Then the section for A is sA=vA*tA+dA
- After that the section for B is sB=vB*tB
When the meeting point will happen at tA=tB
- Now, sA=vA*tB+dA
- After that tB=sB/vB
After that yields:
- Then sA= vA*(sB/vB)+dA
- Then sA-dA= vA*(sB/vB)
- Now, sB= (sA-dA)*vB/vA
- After that tB=((sA-dA)*vB/vA)/vB
- Thus, tB=(sA-dA)/vA
Find out more information about constant speed here:
https://brainly.com/question/12186351